Lycophytes and Monilophytes (Pteridophytes) of the Floresta Nacional de Caxiuanã, Pará State, Brazil: key to the families, and to species of Aspleniaceae and Blechnaceae - Silva, Marcio Roberto Pietrobom da; Rosário, Sebastião Maciel do (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
This study of the Aspleniaceae and Blechnaceae of the Caxiuanã National Forest (FLONA), is part of a series on the floristic, taxonomic and ecological studies of the Lycophyte and Monilophyte flora of the ecosystems of the Brazilian state of Pará. The FLONA is situated in the municipalities of Melgaço and Portel (1º37’S / 51º19’W and 1º54’S / 51º58’W and limits south of 2º15’S / 51º15’W and 2º15’S / 51º56’W) in the micro-region of Furos, in the bay of Caxiuanã, between the Xingu a Tocantins rivers, and occupies about 200.000 ha. The FLONA includes several vegetation types, including non-flooded (terra firme forest with islands of savanna-like and secondary forest) and flooded forest (várzea and igapó), well as abundant aquatic vegetation, the terra firme forest being the predominant type. Taxonomic identification was made following the usual methods and using the specialist literature. Representative specimens were deposited in the “João Murça Pires” (MG) herbarium of the Museu Paraense Emílio Goeldi and duplicates sent to other Brazilian herbaria. A key to the families of Lycophyta and Monilophyta (Pteridophyta) which occur in the area and a taxonomic treatment of the Aspleniaceae and Blechnaceae which occur in the FLONA are presented, with descriptions of the species and genera, illustrations, key to species and genera together with commentaries about the taxa. In the study area the family Aspleniaceae is represented by Asplenium angustum Sw., A. juglandifolium Lam. and A. serratum L. and the family Blechnaceae by Blechnum serrulatum Rich. and Salpichlaena hookeriana (Kuntze) Alston.